Discrete mathematical structures:MCA mathematics volume I - Kundu, Pulak (Kundu Publishers, 2012)
Discrete mathematical structures:MCA mathematics volume I / Kundu, Pulak. -- Kolkata: Kundu Publishers, 2012 511.3 K97 V1 No. of Copies : 1